2013
DOI: 10.5455/2320-6012.ijrms20130815
|View full text |Cite
|
Sign up to set email alerts
|

A randomized control study of yoga on anemic patients

Abstract: 40 Anemic individuals aged between 15-40 years randomly were taken as subjects. They were trained for Trikonasana and its variations, Sarvangasana, Surya namaskara, Yoga mudras for 90 days under supervision of professional yoga trainers. Assessments of various parameters like Pulse rate, B.P, Hb%, were done before the training and after the training of 30 th , 60 th and 90 th day with and without treatment. After yoga with treatment increases Pulse rate and Hb%, while BP was shown normal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 1 publication
0
4
1
Order By: Relevance
“…The reason for increased Hb% can be explained by two different mechanisms: release of erythropoietin due tohypoxia during yoga practices; increased release of iron stores from reticulo-endothelial cells and enhanced release of reserved RBCs by splenic contraction. 25,40 Our study revealed a rise in WBC count though not significant. This is consistent with earlier studies.…”
Section: Discussioncontrasting
confidence: 45%
“…The reason for increased Hb% can be explained by two different mechanisms: release of erythropoietin due tohypoxia during yoga practices; increased release of iron stores from reticulo-endothelial cells and enhanced release of reserved RBCs by splenic contraction. 25,40 Our study revealed a rise in WBC count though not significant. This is consistent with earlier studies.…”
Section: Discussioncontrasting
confidence: 45%
“…The pulse rate is counted and noted per one minute. Blood pressure is measured by using mercuric sphygmomanometer 9 and Hb% is measured by using with Sahli's haemometer.…”
Section: Methodsmentioning
confidence: 99%
“…[26] The effect of yoga on anemic patients was significantly increase hemoglobin content due to increased red blood cell count can be explained by two different mechanisms; it may be due to hypoxia that release more erythropoietin during yoga practices and second is that yoga practices increased release of iron stores from reticulo endothelial cells and spleenic contraction enhance the release of reserved RBCs. [27] Asanas minimizes all types of stress whether it is physical, physiological or psychological as revealed by decreased leukocyte count after yoga [28] , Decline in total WBC count may be due to the concept that hypoxia induced during yoga, increase erythroied series in bone marrow causes relative decrease in WBC count or Yoga may transited the WBC in their resting condition and decrease various cytokines which are responsible for leucopoiesis. [29] , significant improvement of red blood cells count due to effect of yoga [30,31] , cardioprotectant factor of yoga practice increase in hemoglobin may be justified by the anti-stress effect produced by parasympathetic dominance.…”
Section: Discussionmentioning
confidence: 99%